Emotional Self-Regulation through Introjective Practices in Physical Education - Dolors Cañabate; Mónica Santos; David Rodríguez; Teresa Serra; Jordi Colomer (MDPI AG, 2020)
This study analyzed emotional self-regulation in relation to K-9 and K-10 school children's emotional intelligence defined on three dimensions: Emotional attention, clarity of feelings, and emotional repair. The objective was to analyze the students' perceptions of skills and capacities that promoted the awareness of emotions when performing introjective motor practices, i.e., motor skill exercises in which the inner logic provokes a process of sensorial self-awareness and psychosomatic balance. A total of 90 fourth-year primary school students from four different schools participated in the study and a reduced version of the Trait-Meta Mood Scale (TMMS) questionnaire was used to measure students' individual self-regulation. First, pre- and post-test results showed significant differences with a 20.1% improvement in the three dimensions of intrapersonal emotional attention (emotional attention, clarity of feeling, and emotional repair) after having performed a set of in-class introjective practices. Second, while there were no significant differences between the boys and girls during the pre-test, significant changes-an 8.1% difference-were found in the post-test results for girls.